Neonatal Hyperbilirubinemia in infants with G6PD c.563C > TVariant - Moiz Bushra; Nasir Amna; Khan Sarosh; Kherani Salima; Qadir Maqbool (BMC, 2012)
Abstract Background There is a strong correlation between glucose-6-phosphate dehydrogenase (G6PD) deficiency and neonatal hyperbilirubinemia with a rare but potential threat of devastating acute bilirubin encephalopathy. G6PD deficiency was observed in 4-14% of hospitalized icteric neonates in Pakistan. G6PD c.563C > T is the most frequently reported variant in this population. The present study was aimed at evaluating the time to onset of hyperbilirubinemia and the postnatal bilirubin trajectory in infants having G6PD c.563C > T. Methods This was a case-control study conducted at The Aga Khan University, Pakistan during the year 2008. We studied 216 icteric male neonates who were re-admitted for phototherapy during the study period. No selection was exercised. Medical records showed that 32 were G6PD deficient while 184 were G6PD normal. Each infant was studied for birth weight, gestational age, age at the time of presentation, presence of cephalhematoma, sepsis and neurological signs, peak bilirubin level, age at peak bilirubin level, days of hospitalization, whether phototherapy or exchange blood transfusion was initiated, and the outcome. During hospital stay, each baby was tested for complete blood count, reticulocyte count, ABO and Rh blood type, direct antiglobulin test and quantitative G6PD estimation [by kinetic determination of G6PDH]. G6PDgenotype was analyzed in 32 deficient infants through PCR-RFLP analysis and gene sequencing. Results G6PD variants c.563C > T and c.131 C > G were observed in 21 (65%) and three (9%) of the 32 G6PD deficient infants, respectively. DNA of eight (25%) newborns remained uncharacterized. In contrast to G6PD normal neonates, infants with c.563C > T variant had significantly lower enzyme activity (mean ± 1SD; 0.3 ± 0.2 U/gHb vs. 14.0 ± 4.5 U/gHb, p < 0.001) experienced higher peak levels of total serum bilirubin (mean ± 1SD; 16.8 ± 5.4 mg/dl vs. 13.8 ± 4.6 mg/dl, p = 0.008) which peaked earlier after birth (mean ± 1SD 2.9 ± 1.6 vs. 4.3 ± 2.3 days, p = 0.007). No statistically significant difference was observed in mean weight, age at presentation, hemoglobin, reticulocyte count, TSH level, hospital stay or in the frequency of initiation of phototherapy or blood exchange between the two groups. Conclusions We concluded that infants with G6PD c.563C > T variant developed jaundice earlier than infants with normal G6PD enzyme levels. Compared to G6PD normal infants, G6PD c.563C > T carrying infants had significantly low G6PD activity.